Early infant HIV diagnosis and entry to HIV care cascade in Thailand: an observational study. Issue 6 (June 2016) - Sirirungsi, Wasna; Khamduang, Woottichai; Collins, Intira Jeannie; Pusamang, Artit; Leechanachai, Pranee; Chaivooth, Suchada; Ngo-Giang-Huong, Nicole; Samleerat, Tanawan
Summary: Background: Early infant diagnosis of HIV is crucial for timely initiation of antiretroviral therapy (ART) in infected children who are at high risk of mortality. Early infant diagnosis with dried blood spot testing was provided by the National AIDS Programme in Thailand from 2007. We report ART initiation and vital status in children with HIV after 7 years of rollout in Thailand. Methods: Dried blood spot samples were collected from HIV-exposed children in hospitals in Thailand and mailed to the Faculty of Associated Medical Sciences, Chiang Mai University, where HIV DNA was assessed with real-time PCR to establish HIV infection. We linked data from children with an HIV infection to the National AIDS Programme database to ascertain ART and vital status. Findings: Between April 5, 2007, and Oct 1, 2014, 16 046 dried blood spot samples were sent from 8859 children in 364 hospitals in Thailand. Median age at first dried blood spot test was 2·1 (IQR 1·8–2·5) months. Of 7174 (81%) children with two or more samples, 223 (3%) were HIV positive (including five unconfirmed). Of 1685 (19%) children with one sample, 70 (4%) were unconfirmed positive. Of 293 (3%) children who were HIV positive, 220 (75%) registered for HIV care and 170 (58%) initiated ART. Median age at ART initiation decreased from 14·2 months (IQR 10·2–25·6) in 2007 to 6·1 months (4·2–9·2) in 2013, and the number of children initiating ART aged younger than 1 year increased from five (33%) of 15 children initiating ART in 2007 to ten (83%) of 12 initiating ART in 2013. 15 (9%) of 170 children who initiated ART died and 16 (32%) of 50 who had no ART record died. Interpretation: Early infant diagnosis with dried blood spot testing had high uptake in primary care settings. Further improvement of linkage to HIV care is needed to ensure timely treatment of all children with an HIV infection. Funding: None.